Salvation in the Letter of St. Paul to Romans - Kilonzo, Felix Munyao (2022)
The letter to the Romans is the longest letter that Paul wrote to a community that he did not found. It is with no doubt that, he is the author of the letter. In this letter, the underlying theme is the coherence of God’s faithfulness along the history of salvation. Along the main theme, there are other themes, which Paul devolve. One of the theme that is very evident from the beginning of the letter is the theme of salvation. Our work is as result of a theological reflection on the theme of salvation in the letter. Paul presents the doctrine of a universal salvation with use of pas (all) in the Romans, which offers ground for the universal salvation that Paul emphasizes. It is clear to note that Paul’s soteriology in this letter is Christological as well as eschatological. This is evident with the use of verb sodzo (to save) in the future tense in all verses in the letter. Therefore, in our reflection, we shall analyse verses in which this verb appear, for better understanding of the theme of salvation. This work will show the development of Paul’s theme of salvation from justification to reconciliation, from hope of salvation to assurance of salvation and from salvation of the remnant to salvation of “all Israel”.